Responsibility and Accountability of University Social and Environmental Performances: A Sustainability Balanced Scorecard Model - Imanda Firmantyas Putri Pertiwi; Rosana Eri Puspita; Saifudin Saifudin (Shirkah: Journal of Economics and Business, 2021)
Since research on the use of sustainability balanced scorecard to assess university social and environmental performances still remains unexplored, this study aims to fill the gap by examining the acceptance of the idea of the State Islamic Religious Colleges (PTKIN) performances in terms of responsibility for social and environmental aspects based on the sustainability balanced scorecard model. Drawing on a qualitative research, eight respondents from the Board of National Accreditation for Higher Education (BAN-PT) and PTKIN policymakers were interviewed. The results indicated that PTKIN must pay more attention to social and environmental perspectives. It was further revealed that although BAN-PT regulation has explicitly included these two perspectives, there were several indicators that still need to be added according to the sustainability balanced scorecard model. Moreover, the results depicted several challenges such as budgeting, regulations, and paradigms that required some adjustment from the policymakers. These results contribute as fruitful insights for university policymakers in developing strategies to enhance university performances, particularly in social and environmental aspects.